SOLVENT SUPPRESSION IN FOURIER-TRANSFORM NUCLEAR MAGNETIC-RESONANCE - Hore, P (1983)
New pulse sequences for solvent suppression in Fourier transform NMR are derived and evaluated. They are designed to be insensitive to the most common spectrometer imperfections so as to give efficient elimination of a solvent resonance without fine adjustment of experimental conditions. The most satisfactory sequences consist of equally spaced hard pulses with lengths in the ratio of binomial coefficients and phases alternating between 0 and 180°. In particular the sequence 131 or α(X)-τ-3α(-X)-τ-3α(X)-τ-α(-X) is shown to be very successful, giving solvent suppressions of more than 1000-fold. © 1983.